Metabolism and Nutritive Role of Cholesterol in the Growth, Gonadal Development, and Reproduction of Crustaceans. Issue 2 (3rd April 2018) - Kumar, Vikas; Sinha, Amit Kumar; Romano, Nicholas; Allen, Kristy M.; Bowman, Benjamin A.; Thompson, Kenneth R.; Tidwell, James H.
ABSTRACT: Cholesterol is a major sterol in crustaceans that occurs in all cells and in the hemolymph, either in free form or combined with fatty acids. Unlike vertebrates, shrimps and other crustaceans are incapable of de novo synthesis of cholesterol; therefore, dietary cholesterol is essential for their growth and survival. Their requirement, however, is often species-specific and may also depend on the dietary protein and lipid sources. Dietary lipid sources can include the presence of phytosterols and phospholipids, which may have a cholesterol sparing effect in some species. On the other hand, compounds found within some fishmeal alternatives may disrupt cholesterol utilization. Understanding these relationships is important because cholesterol is essential for the synthesis of ecdysteroids and sesquiterpenoids, which are a class of hormones that regulate moulting and reproduction in crustaceans. The biosynthetic pathway of these hormones is not completely understood in crustaceans. When knowledge gaps exist, available information from a better-studied animal group (the insect), is extrapolated to produce a hypothetical model of putative ecdysteroid synthesis in crustaceans. The key steps in cholesterol metabolism, including digestion, absorption, and transportation are highlighted. There is also a focus on various pathways involving candidate genes (encoding enzymes) linking cholesterol metabolism and moulting. Considering the relatively high cost of cholesterol, a better understanding of factors influencing dietary cholesterol requirements in crustaceans and role this plays in lipid metabolism may facilitate more cost-effective feed formulations.